2021
DOI: 10.4081/reumatismo.2021.1358
|View full text |Cite
|
Sign up to set email alerts
|

Denosumab for the treatment of HIV-associated osteoporosis with fractures in a premenopausal woman

Abstract: The prevalence of osteoporosis is about three times greater in people living with HIV than in the general population. Bisphosphonates are the only class of antiresorptive drugs which have proved to be safe and effective in HIV patients. However, bisphosphonates are not recommended in women of childbearing age due to an increased rate of associated neonatal complications. To the best of our knowledge no reports on the use of denosumab in HIV-infected individuals have been published so far. We describe a 38 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Experts from the HIV consensus proposal ( 31 ) recommend that patients at a high risk of fracture (brittle fracture, osteoporosis, bone loss, or an elevated FRAX score) avoid using nucleotide reverse transcriptase inhibitors and protease inhibitors and instead implement diet and lifestyle management strategies such as calcium supplementation (500–600 mg/day), cholecalciferol (800–1200 IU/day), and anti-osteoporosis therapy. Although bisphosphonates can reportedly improve BMD ( 32 , 33 ), the use of teriparatide ( 34 ) and denosumab ( 35 ) has only been reported in a few cases.…”
Section: Discussionmentioning
confidence: 99%
“…Experts from the HIV consensus proposal ( 31 ) recommend that patients at a high risk of fracture (brittle fracture, osteoporosis, bone loss, or an elevated FRAX score) avoid using nucleotide reverse transcriptase inhibitors and protease inhibitors and instead implement diet and lifestyle management strategies such as calcium supplementation (500–600 mg/day), cholecalciferol (800–1200 IU/day), and anti-osteoporosis therapy. Although bisphosphonates can reportedly improve BMD ( 32 , 33 ), the use of teriparatide ( 34 ) and denosumab ( 35 ) has only been reported in a few cases.…”
Section: Discussionmentioning
confidence: 99%
“…In a case report of a 38-year-old woman living with HIV, denosumab treatment given for 4 years was associated with an increase in BMD and a decrease in bone fracture without reactivation of opportunistic infection or HIV infection [ 113 ]. Wheeler et al showed in a case report that Teriparatide is safe and effective for the treatment of osteoporosis in PLWHIV [ 114 ].…”
Section: Anti-osteoporotic Drugsmentioning
confidence: 99%
“…Additionally, single case report of prolonged denosumab in a premenopausal WLWH found it to be safe and effective [93]. However, a rebound phenomenon on discontinuation, with a three‐ to five‐fold increased risk for some fractures, has been observed in the general population[94] and so caution should be taken in prescribing. This risk/benefit is more of a consideration in younger patients, which has particular relevance for PLWH.…”
Section: Clinical Guidance For Bone Health Screening and Interventionmentioning
confidence: 99%